2018
DOI: 10.3390/ijerph15061162
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Hazardous Chemical Exposure Control System at a Semiconductor Manufacturing Company in South Korea

Abstract: The goal of this study was to evaluate the hazardous chemical exposure control system in a semiconductor manufacturing company and recommend an appropriate exposure surveillance system for hazardous agents. We reviewed compliance-based chemical exposure data compiled between 2012 and 2014 by the study company. The chemical management system, characteristics of chemical use and hazardous gas monitoring system were also investigated. We evaluated the airborne isopropyl alcohol (IPA) and acetone generally used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Japanese workers work so long and hard, occupational chemical exposure may strongly influence cancer incidence in Japan (Kaneko et al, 2019). Employees working in manufacturing conditions have a greater potential to genotoxic overexposure than those in other working categories (Choi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Japanese workers work so long and hard, occupational chemical exposure may strongly influence cancer incidence in Japan (Kaneko et al, 2019). Employees working in manufacturing conditions have a greater potential to genotoxic overexposure than those in other working categories (Choi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Data on chemical exposure in industrial working environments or due to accidents are collected and reported in various government offices. However, there are no data on chemical exposure in everyday life in South Korea [10]. Almost all patients complaining of acute chemical exposure are admitted to the ED, but people facing chronic exposure to chemicals because of unsafe work environments may not visit the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Data on chemical exposure in industrial working environments or due to accidents are collected and reported in various government offices. However, there are no data on chemical exposure in everyday life in South Korea [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…are repeated several times. There were divided into four main groups: (1) photolithography and etching; (2) diffusion and ion implantation; (3) deposition-epitaxial or chemical vapor deposition (CVD); and (4) metallization-sputtering and evaporation [24]. If each document could be classified in detail, photolithography and diffusion processes were separately defined as specific processes.…”
Section: Methodsmentioning
confidence: 99%